Characterisation of ball impact conditions in professional tennis: Matches played on hard court - Lane, B.; Sherratt, P.; Xiao, H.; Harland, A. (Proceedings of the Institution of Mechanical Engineers, Part P: Journal of Sports Engineering and Technology, 2016)
To assess ball performance for research and development purposes requires greater understanding of the impact conditions a tennis ball experiences in professional tournament play. Ball tracking information taken from three consecutive years of an ATP 250 tour event played on hard court was analysed. The frequency of first serves, second serves, racket impacts and surface impacts was assessed per game and extrapolated to show how many impacts a single ball is subjected to. Where applicable the pre- and post-impact velocities and angles were found, and the distribution of each was analysed. In total, data from 65 matches comprising 1505 games were analysed. On average, each game contained 70.26 (±16.23) impacts, of which 9.23%, 3.16%, 37.78% and 49.83% were first serves, second serves, racket impacts and surface impacts, respectively. As a result, assuming all balls in play are used evenly, a single ball is expected to be subjected to 105 (±24) impacts over the course of the nine games that it is in play. The results of the investigation could be used to design a wear protocol capable of artificially wearing tennis balls in a way that is representative of professional play.